CAREER WOMAN AND HER WORK-LIFE BALANCE - Arestia, Nova (Universitas Riau Kepulauan, 2023)
The purpose of this study was to examine about the work-life balance of a career woman. The target for this study is women who have jobs, both married and unmarried, and already have children or do not have children. The method used in this research is a form of descriptive research, with quantitative data analysis techniques and data collection tools that use questionnaire tools and literature studies. Before being widely disseminated, the statement items on the questionnaire were tested for validity and reliability using the SPSS 26 program. The questionnaire was distributed through Google Forms and filled out by 74 respondents. The respondents who filled in came from various ages and with varying periods of work. The results showed that most respondents already had a good work-life balance and three aspects of work-life balance were fulfilled even though they were not greatly optimized. It is highly recommended that career women must be paying attention to work-life balance, so as not to feel pressured and experience work dissatisfaction in carrying out their dual roles.